Globalising the Climate : COP21 and the climatisation of global debates. - Aykut, Stefan C. (Routledge advances in climate change research., 2017)
"Frequently presented as a historic last chance to set the world on a course to prevent catastrophic climate change, the 21st Conference of the Parties to the Climate convention (COP21) was a global summit of exceptional proportions. Bringing together negotiators, scientists, journalists and representatives of global civil society, it also constituted a privileged vantage point for the study of global environmental governance "in the making". This volume offers readers an original account of the current state of play in the field of global climate governance. Building upon a collaborative research project on COP21 carried out by a multidisciplinary team of twenty academics with recognised experience in the field of environmental governance, the book takes COP21 as an entry point to analyse ongoing transformations of global climate politics, and to scrutinise the impact of climate change on global debates more generally. The book has three key objectives:To analyse global climate governance through a combination of long-term analysis and on-sight observation;To identify and analyse the key spaces of participation in the global climate debate;To examine the "climatisation" of a series of crosscutting themes, including development, energy, security and migration. This book will be of great interest to students, scholars and policymakers of climate politics and governance, international relations and environmental studies."--Provided by publisher.